Pengaruh EPS, Suku Bunga, Tingkat Inflasi Terhadap Harga Saham Perusahaan Perbankan di BEI - Desi Astika Rahmadonna; Tutut Dewi Astuti (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The aim of this research was to show knowledge about whether or not there is an influence of Earning Per Share, interest rates and inflation rates on the share prices of banking companies on the Indonesian Stock Exchange. All banking companies listed on the Indonesian Stock Exchange, of which there are 47 companies, will be used as the research population which will later be used in testing. In taking the sample, a purposive sampling method will be used, which after consideration is made according to the criteria, a sample of 34 banking companies is produced. In testing variables, analytical techniques are used, namely the classic assumption test which is divided into four, including: normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Multiple linear analysis will also be used, as well as a partial significance test (t test). The results obtained after conducting the research showed that after testing the three dependent variables, only Earning Per Share had a significant and positive influence on the share prices of banking companies listed on the Indonesian Stock Exchange. The test results show that the significance value of the Earning Per Share variable is 0.000 and has a positive beta value, the value states that the significance is smaller than the value of 0.05. Meanwhile, the interest rate and inflation rate variables have no influence on the share prices of banking companies listed on the Indonesian Stock Exchange. The test results show that the value of the significance of the interest rate variable is 0.372 and the value of the significance of the inflation rate variable is 0.706, both of which have significance values ​​greater than 0.05.